Pricing privacy – the right to know the value of your personal data. Issue 2 (April 2018) - Malgieri, Gianclaudio; Custers, Bart
Abstract: The commodification of digital identities is an emerging reality in the data-driven economy. Personal data of individuals represent monetary value in the data-driven economy and are often considered a counter performance for "free" digital services or for discounts for online products and services. Furthermore, customer data and profiling algorithms are already considered a business asset and protected through trade secrets. At the same time, individuals do not seem to be fully aware of the monetary value of their personal data and tend to underestimate their economic power within the data-driven economy and to passively succumb to the propertization of their digital identity. An effort that can increase awareness of consumers/users on their own personal information could be making them aware of the monetary value of their personal data. In other words, if individuals are shown the "price" of their personal data, they can acquire higher awareness about their power in the digital market and thus be effectively empowered for the protection of their information privacy. This paper analyzes whether consumers/users should have a right to know the value of their personal data. After analyzing how EU legislation is already developing in the direction of propertization and monetization of personal data, different models for quantifying the value of personal data are investigated. These models are discussed, not to determine the actual prices of personal data, but to show that the monetary value of personal data can be quantified, a conditio-sine-qua-non for the right to know the value of your personal data. Next, active choice models, in which users are offered the option to pay for online services, either with their personal data or with money, are discussed. It is concluded, however, that these models are incompatible with EU data protection law. Finally, practical, moral and cognitive problems of pricing privacy are discussed as an introduction to further research. We conclude that such research is needed to see to which extent these problems can be solved or mitigated. Only then, it can be determined whether the benefits of introducing a right to know the value of your personal data outweigh the problems and hurdles related to it.